The Teaching and Learning of Statistics International Perspectives - Ben-Zvi, Dani; Makar, Katie (Springer International Publishing : Imprint: Springer, 2016)
This stimulating overview of current innovations in teaching and learning statistics reflects both ongoing trends in the field and the increasing relevance of statistics in our data-driven era. A global panel of scholars, educators, and researchers documents wide-scale challenges such as students integrating statistical and contextual knowledge and teachers developing statistical literacy. The editors and contributors make it clear that the wider uses of statistics are not only applicable to the STEM subjects, but also to critical thinking and reasoning across disciplines, tasks, and interests. The diversity of statistics education is itself on display in terms of curriculum choices, pedagogical strategies, assessment methods, and technological support. Among the topics covered: Learning to integrate statistical and work-related reasoning. Mathematical modeling for critical statistics education. Connections between statistical thinking and critical thinking. Students' sense-making of graphical representation in a basic statistics module. Undergraduate students' conceptions of variability in a dynamic computer-based environment. Preservice teachers' difficulties with statistical writing. Teaching and Learning Statistics captures a watershed moment in education, and is a worthy resource for mathematics teachers and researchers, particularly those interested in statistics education. .